Strategi Peningkatan dan Pertanggungjawaban Dana pada Panti Asuhan Darul Hikmah Gubeng Surabaya Jawa Timur - R. Muh. Syah Arief Atmaja Wijaya; Diah Hari Suryaningrum; Munari Munari; Zidan Ardiansyah; Alexa Nora Soraya; Meylina Amelia Ardi; Melati Cahyaning; Faizah Mahdiyyah Fiddien (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service activity aims to enhance transparency and strategic fund management at the Darul Hikmah Gubeng Orphanage in Surabaya by leveraging digital technology and strengthening the institution’s branding capabilities. A participatory approach was implemented through training in visual content creation using Canva and CapCut, as well as outreach on the QRIS-based digital donation system. Evaluation, conducted through questionnaires and group discussions, demonstrated an increase in the administrators’ understanding of the concepts of accountability, public reporting, and digital communication skills. The results of the activity indicate that the social branding strategy and reporting through social media contributed significantly to building donor trust and expanding the community support network. This model is expected to be replicated in other social institutions with similar needs.